THE IMPACT OF TOXIC COMPOUNDS RELEASED INTO THE ATMOSPHERE ON THE NATIONAL ECONOMY (Archive of Conferences, 2021)
This article highlights the negative impact of toxic compounds released into the atmosphere on the human body, agriculture, and society as a whole, and outlines some methods of eliminating.